1986
DOI: 10.1002/1097-0142(19860901)58:5<1024::aid-cncr2820580507>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate dose methotrexate in childhood acute lymphoblastic leukemia resulting in decreased incidence of testicular relapse

Abstract: Six hundred thirty-four children with acute lymphoblastic leukemia (ALL) were randomized to receive sanctuary therapy consisting of either cranial irradiation (CRT) plus intrathecal (IT) methotrexate (MTX) or three courses of intermediate-dose methotrexate (IDM) plus intrathecal methotrexate. Two hundred sixty-six male patients achieved a complete response and were evaluable for the effects of prophylactic therapy on the duration of remission. There was one isolated testicular relapse (0.8%) in the IDM group c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
0
29
1
Order By: Relevance
“…For instance, it has been shown that methotrexate concentration in the testicular interstitial fluid is twofold to fourfold lower than in the serum. The concentration [23]. Though a physiologic barrier may explain these findings, other studies have suggested that the testes' external location may contribute to the decreased efficacy of leukemia therapy.…”
Section: The Cns and Testes: The Physiology Behind Relapsementioning
confidence: 99%
See 3 more Smart Citations
“…For instance, it has been shown that methotrexate concentration in the testicular interstitial fluid is twofold to fourfold lower than in the serum. The concentration [23]. Though a physiologic barrier may explain these findings, other studies have suggested that the testes' external location may contribute to the decreased efficacy of leukemia therapy.…”
Section: The Cns and Testes: The Physiology Behind Relapsementioning
confidence: 99%
“…A barrier between the blood and the seminiferous tubules has been identified [22]. Leukemic cells, however, are usually found in the interstitial space, and a clear barrier between the blood and the interstitial space has not been well defined [22,23]. There is evidence, however, that systemic medications may not be equally distributed into the testes.…”
Section: The Cns and Testes: The Physiology Behind Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…21,22 In addition, high dosages of MTX offer the advantage of targeting extramedullary leukemia by producing cytotoxic concentrations in sanctuary sites where low-dose MTX does not readily distribute (eg, testes, cerebrospinal fluid). 10,23 However, the optimal dose of MTX, the adequate duration of the drug infusion, and the adequate folinic acid rescue remain controversial. 1,[24][25][26][27][28] While one randomized trial indicated that patients at increased risk of relapse treated initially with high-dose MTX (4 g/m 2 ) had significantly better event-free survival (EFS) rates compared with patients treated with low-dose MTX (40 mg/m 2 ), 24 ultra-high-dose MTX (12 g/m 2 ) at a 4-hour infusion and an intensive folinic acid rescue was not found to be beneficial in relapsed ALL children, compared with intermediate-dose MTX (1 g/m 2 ) at a 36-hour infusion and a reduced folinic acid rescue.…”
Section: Introductionmentioning
confidence: 99%